Two-photon excitation of two Rydberg levels of O2 above 95 130 cm–1: Rotational-state dependence of predissociation linewidths. (March 2020) - Kono, Mitsuhiko; He, Yabai; Lewis, Brenton R.; Gibson, Stephen T.; Baldwin, Kenneth G.H.; Orr, Brian J.
Highlights: We report two-photon spectra of J ′=0 and J ′=1 Rydberg levels in O2 above 95 130 cm –1 Molecular beam and narrowband UV laser source yield 0.006-cm –1 spectral bandwidth. This enables new measurements of J ′-dependent lineshapes and predissociation rates. We propose J ′-dependent predissociation schemes due to perturbing valence manifolds. Abstract: Two-photon absorption is employed to record sub-Doppler molecular-beam spectra of oxygen ( 16 O2 ), excited to the υ ' = 1 level of its ( X   2 Π g ) 5 d π 1 Σ g + Rydberg state above 95 130 cm –1 and detected by photoionisation in a time-of-flight instrument. A nonlinear-optical source generates single-longitudinal-mode pulses of coherent ultraviolet light at ∼210 nm with sufficiently narrow optical bandwidth to enable more detailed lineshape measurements of rovibronic features than had been achieved in an early investigation [Pratt et al., J. Chem. Phys. 1990; 93: 3072–84]. A spectral width of 0.59 ± 0.02 cm –1 is derived by Lorentzian and Beutler-Fano lineshape fits to the prominent P Q 13 (0) feature, nominally at ∼95 133.7 cm –1 in that spectrum; our estimated width is significantly narrower than the previously reported width of ∼1.0 cm –1 . Likewise, the adjacent R Q 11 (2) feature, nominally at ∼95 143.8 cm –1, is found to be markedly broader (2.2 ± 1.5 cm –1 ), which is consistent with the supposed effects of J ′-dependent predissociation arising from overlap between the ( X   2 Π g ) 5 d π 1 Σ g + Rydberg manifold and other dissociative states. The dependence of the O2 + and O + ion signals on acceleration voltages, O2 -jet stagnation pressure, ultraviolet pulse energy and optical polarisation are also examined.